(untitled) (REVISTA NODO, 2024)
In the works that make up this dossier, the artist Oliver Ressler (Austria, 1970) replaces the concept of “participatory democracy”—which had characterized works such as the emblematic What is Democracy? (2009)—for “climate justice,” with films in which the protagonist is the emergency in the face of global warming caused by greenhouse gases, and perhaps for the “utopia” of building a world without CO2 emissions. before the year 2050.